2023
DOI: 10.1101/2023.11.30.569344
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Patterns and correlates in the distribution, design and management of garden ponds along an urban-rural gradient

Andrew J. Hamer,
Barbara Barta,
Zsuzsanna Márton
et al.

Abstract: Urbanisation results in the loss and alteration of natural wetlands and ponds. However, garden ponds in cities and towns can act as rich reservoirs of aquatic biodiversity and stepping stones for dispersal. Homeowners with a range of different motivations, including biodiversity values, install garden ponds. Here, our main aim was to study whether the design and management choices of garden pond owners was dependent on the location of ponds (capital city vs. countryside), when ponds were installed (pond age), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Despite the introduction of fish into 85% of ponds, amphibian reproduction was observed in 60% of the ponds, indicating that some species are able to co-exist with fish (Hamer et al, 2021; Kloskowski et al, 2020). In another study focusing on local pond features in the same set of ponds, it was also found that the introduction of fish was a significant predictor of garden pond design and within-pond features including management practices (Hamer et al, 2023). This result implies a potential conflict between creating ponds with the main aim of keeping ornamental fish and the potential of garden ponds to support native biodiversity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the introduction of fish into 85% of ponds, amphibian reproduction was observed in 60% of the ponds, indicating that some species are able to co-exist with fish (Hamer et al, 2021; Kloskowski et al, 2020). In another study focusing on local pond features in the same set of ponds, it was also found that the introduction of fish was a significant predictor of garden pond design and within-pond features including management practices (Hamer et al, 2023). This result implies a potential conflict between creating ponds with the main aim of keeping ornamental fish and the potential of garden ponds to support native biodiversity.…”
Section: Discussionmentioning
confidence: 99%
“…Many amphibian species prefer well-vegetated or large ponds (Arntzen et al, 1997; Péntek et al, 2017; Rannap et al, 2013), which was supported by our results that several species such as Bombina bombina, Pelobates fuscus, Triturus dobrogicus were positively associated with aquatic vegetation in our ponds. Due to the larger size of the rubber-lined ponds, rubber substrate had a significantly positive effect on the presence of amphibians and their tadpoles, also odonates, birds, and wading birds (Hamer et al, 2023).…”
Section: Discussionmentioning
confidence: 99%